A four-helix bundle DNA nanostructure with binding pockets for pyrimidine nucleotides. Issue 21 (22nd March 2017) - Schwarz, Rainer Joachim; Richert, Clemens
Abstract : A DNA nanostructure with a number of residues typical for protein enzymes folds stably and in high yield, starting from synthetic oligonucleotides and can be used to set up high-affinity binding sites. Abstract : Designed DNA nanostructures of impressive size have been described, but designed structures of the size of protein enzymes that bind organic ligands with high specificity are rare. Here we report a four-helix motif consisting of three synthetic strands with 65 base pairs and 165 nucleotides in total that folds well. Furthermore, we show that in the interior of this small folded DNA nanostructure, cavities can be set up that bind pyrimidine nucleotides with micromolar affinity. Base-specific binding for both thymidine and cytidine derivatives is demonstrated. The binding affinity depends on the position in the structure, as expected for recognition beyond simple base pairing. The folding motif reported here can help to expand DNA nanotechnology into the realm of selective molecular recognition that is currently dominated by protein-based enzymes and receptors.